Konsensualne zakończenie postępowania przygotowawczego w trybie art. 355 k.p.k. - Kowalczyk, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper focuses on in-court settlement under Article 335 of the Code of Criminal Procedure and its procedural consequences. In particular, the author presents the findings of theory and practice resulting from an analysis of case law concerning the functioning of the consensual mode of proceedings in the Polish Criminal procedure.
Keywords: postępowanie karne; sposoby konsensualne; ugoda sądowa